Visual Propaganda as a Foreign Policy Tool of the Islamic Republic of Iran in Relations with the State of Israel - Tarasiuk, Renata (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2023)
The main purpose of this article is the explanation of the relationship between satirical drawing as a propaganda tool and the vectors of the international policy of the Islamic Republic of Iran, with particular emphasis on the State of Israel.. The subject of the description is the use of satirical drawing by Iranian cultural institutions in creating anti-Israel policy and striving for its broadest visibility in an international perspective. Propaganda, due to its persuasive potential, transforming perception and leading to manipulation of behaviors, requires appropriate tools with which symbols, slogans and keywords are activated to – paraphrasing John Austin – create the desired reality with the help of an appropriate narrative. The article adopts the hypothesis that Iranian visual propaganda plays an important role in creating an anti-Israel discourse. Detailed research questions focus on the way in which Iran uses images (icons/ symbols) to implement its anti-Israel campaign, institutions constructing propaganda discourse, situations conducive to creating such discourses, and the nature of relations between propaganda and other political activities towards Israel, as well as towards USA. The article refers to selected contents of visual propaganda which, according to the author, refer to the most important aspects of Iranian-Israeli relations (in the Iranian-American context as well), including in particular the importance of the Holocaust remembrance policy and its relation to the contemporary Middle East situation, especially the Palestinian problem. In the empirical process, the visual forms of propaganda discourse were analyzed in terms of hybrid multisemiotic structures, and in the theoretical part, the most commonly used classical formal methods in this type of research were used.